2018
DOI: 10.1021/acscatal.8b00906
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Biaryl Atropisomers via the Addition of Thiophenols into Aryl-Naphthoquinones

Abstract: We report a cinchona alkaloid catalyzed addition of thiophenol into rapidly interconverting aryl-naphthoquinones, resulting in stable biaryl atropisomers upon reductive methylation. An array of thiophenols and naphthoquinone substrates were evaluated, and we observed selectivities up to 98.5:1.5 e.r. Control of the quinone redox properties allowed us to study the stereochemical stabilities of each oxidation state of the substrates. The resulting enantioenriched products can also be moved on via an SNAr-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 47 publications
(58 reference statements)
2
19
0
Order By: Relevance
“…As both sulfoxide and sulfone are biologically active pharmacophores found in many pharmaceutical activities, we next investigated functionalizing compounds 2 / 2 ' to the corresponding 4‐sulfoxide‐substituted and 4‐sulfone‐substituted isochromenones by treating compound 2 / 2' with m ‐CPBA , . As expected, the obtained 4‐(methylthio)isochromenones and deuterated 4‐(methylthio)isochromenones can be further converted into the corresponding sulfoxide or sulfone compounds smoothly, demonstrating the broader application prospect of the method (Table ).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As both sulfoxide and sulfone are biologically active pharmacophores found in many pharmaceutical activities, we next investigated functionalizing compounds 2 / 2 ' to the corresponding 4‐sulfoxide‐substituted and 4‐sulfone‐substituted isochromenones by treating compound 2 / 2' with m ‐CPBA , . As expected, the obtained 4‐(methylthio)isochromenones and deuterated 4‐(methylthio)isochromenones can be further converted into the corresponding sulfoxide or sulfone compounds smoothly, demonstrating the broader application prospect of the method (Table ).…”
Section: Resultsmentioning
confidence: 71%
“…of m ‐CPBA delivered sulfoxides 3a , 3e and 3b' in good yields . Furthermore, when the amount of the oxidant was increased to 3.0 equiv., 2 / 2' can be converted into the corresponding sulfones 4a , 4e and 4b' in a yield of 89 %, 85 % and 80 % respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiophenol (PhSH) and its derivatives are highly reactive aromatic thiols which care extensively used in the chemical industry for preparing pesticides, polymers, and pharmaceuticals [1,2,3]. Despite its critical and widespread usage, PhSH is also highly toxic to organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our group has focused on the atroposelective synthesis of naphthoquinone-based biaryls via the rigidification of a rapidly interconverting axis via a 1,4-nucleophilic addition into the quinone. 28 As there is a lack of enantioselective routes towards atropisomeric diaryl ethers, we decided to test whether this approach could be extended to this scaffold (Scheme 1B). We chose to evaluate naphthoquinones such as 1a where the aryl groups possessed a large tert -butyl group and a 2 nd smaller substituent ortho -to the ether axis, as Clayden has shown that having one large quaternary substituent is often a prerequisite to obtain stereochemically stable diaryl ethers.…”
mentioning
confidence: 99%